Tissue factor associates with survival and regulates tumour progression in osteosarcoma - Tieken, Chris; Verboom, Michiel C.; Ruf, Wolfram; Gelderblom, Hans; Bovée, Judith V. M. G.; Reitsma, Pieter H.; Cleton-Jansen, Anne-Marie; Versteeg, Henri H. (Thrombosis and Haemostasis, 2016)
Osteosarcoma is the most common primary malignant bone tumour. Patients often develop lung metastasis and have a poor prognosis despite extensive chemotherapy and surgical resections. Tissue Factor is associated with poor clinical outcome in a wide range of cancer types, and promotes angiogenesis and metastasis. The role of Tissue Factor in OS tumourigenesis is unknown. Fifty-three osteosarcoma pre-treatment biopsies and four osteosarcoma cell lines were evaluated for Tissue Factor expression, and a possible association with clinical parameters was investigated. Tissue Factor function was inhibited in an osteosarcoma cell line (143B) by shRNA knockdown or specific antibodies, and pro-tumourigenic gene expression, proliferation, matrigel invasion and transwell migration was examined. 143B cells were implanted in mice in the presence of Tissue Factor-blocking antibodies, and tumour volume, micro-vessel density and metastases in the lung were evaluated. Tissue Factor was highly expressed in 73.6 % of osteosarcoma biopsies, and expression associated significantly with disease-free survival. Tissue Factor was expressed in all four investigated cell lines. Tissue Factor was knocked down in 143B cells, which led to reduced expression of IL-8, CXCL-1, SNAIL and MMP2, but not MMP9. Tissue Factor knockdown or inhibition with antibodies reduced matrigel invasion. Tissue Factor antibodies limited 143B tumour growth in vivo, and resulted in decreased intra-tumoural micro-vessel density. Furthermore, lung metastasis from the primary tumour was significantly reduced. Thus, Tissue Factor expression in osteosarcoma reduces metastasis-free survival in patients, and increases pro-tumourigenic behaviour both in vitro and in vivo.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Osteosarcoma; coagulation; tumour; migration